2016
DOI: 10.3109/24701394.2016.1155051
|View full text |Cite
|
Sign up to set email alerts
|

DNA Mini-barcoding for wildlife trade control: a case study on identification of highly processed animal materials

Abstract: Although DNA barcoding is an efficient tool for species identification, however, its efficiency is uncertain for samples having degraded DNA and incomplete isolation/amplification of COI gene fragment (>500 bp). DNA mini-barcoding is a solution to this problem because small DNA fragment of COI genes is used for species identification. Twelve highly processed, chemically treated and finished animal skin (coats, tanned skins) and fur (mufflers) samples, received from the Sindh Wildlife Department, Pakistan, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…The results were consistent with a previously reported study that identified G. gecko from adulterants using COI regions [11,22]. DNA minibarcoding and specific-PCR identification are becoming more popular methods for effective species identification [24,25,31], especially for specimens with degraded DNA, such as archival specimens, processed foods, functional foods, and Chinese patent medicines [26,27,[32][33][34][35]. For a more sensitive identification of G. gecko in Fig.…”
Section: Discussionsupporting
confidence: 91%
“…The results were consistent with a previously reported study that identified G. gecko from adulterants using COI regions [11,22]. DNA minibarcoding and specific-PCR identification are becoming more popular methods for effective species identification [24,25,31], especially for specimens with degraded DNA, such as archival specimens, processed foods, functional foods, and Chinese patent medicines [26,27,[32][33][34][35]. For a more sensitive identification of G. gecko in Fig.…”
Section: Discussionsupporting
confidence: 91%
“…The results were consistent with a previously reported study that identi ed G. gecko from adulterants using COI regions [11,22]. DNA mini-barcoding and speci c-PCR identi cation are becoming more popular methods for effective species identi cation [24,25,31], especially for specimens with degraded DNA, such as archival specimens, processed foods, functional foods, and Chinese patent medicines [26,27,[32][33][34][35]. For a more sensitive identi cation of G. gecko in 2001, it was distinguished from 14 adulterants through allele-speci c diagnostic PCR which ampli ed 260-bp fragments of the 12S rRNA gene [36].…”
Section: Discussionsupporting
confidence: 91%
“…Genetic analyses have become a powerful analytical tool to elucidate the species identity and trace the geographic origin of various valuable artefacts of biogenic origin. These include processed products of tortoise shell 22 , snake skin 23 , fur 24,25 , ivory 26,27 or tiger bones 28 . Of greatest relevance to this present study, Meyer, et al 29 reported quasi-nondestructive species identification of pearls based on DNA analysis, where so little amount of pearl material was used for the analyses that the market value of the pearl was not compromised.…”
mentioning
confidence: 99%